2017
DOI: 10.1080/02699052.2017.1283533
|View full text |Cite
|
Sign up to set email alerts
|

Depression in youth recovering from concussion: Correlates and predictors

Abstract: Depression is commonly reported in this subset of children. High post-concussive symptom scores and hospital admission were strong predictors of depression. Screening for depression should be standard practice in concussion management in children and youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 47 publications
4
33
1
Order By: Relevance
“…Studies have reported an association between depression and concussion, 50 as well as increases in risk of depression after either a single or multiple concussions. [51][52][53] In addition, there is evidence for a relationship between depression and persistent symptoms of concussion, 54 and treatments for depression (such as cognitive-behavioral therapy and medication) have been found to be beneficial for treating youth with persistent concussion symptoms. 55 In sum, the relationship between depression and concussion is complex and this study adds important data on younger players.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported an association between depression and concussion, 50 as well as increases in risk of depression after either a single or multiple concussions. [51][52][53] In addition, there is evidence for a relationship between depression and persistent symptoms of concussion, 54 and treatments for depression (such as cognitive-behavioral therapy and medication) have been found to be beneficial for treating youth with persistent concussion symptoms. 55 In sum, the relationship between depression and concussion is complex and this study adds important data on younger players.…”
Section: Discussionmentioning
confidence: 99%
“…3 Youth with concussion can experience both short-term and long-term physical, emotional, cognitive and sleep-related symptoms. 4 5 Although individual symptoms can vary, 5 6 researchers have consistently identified negative effects on academics, [7][8][9][10] physiological functioning, [11][12][13][14] psychological well-being [15][16][17] and overall quality of life. 18 Best practices for managing concussion include education to promote appropriate knowledge, attitudes and behaviours among stakeholders (eg, students, parents, school staff and healthcare providers), 19 20 interventions to manage recovery 21 22 and protocols to support students returning to academics and school sports.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 A recent prospective cohort study of youth with concussion found that 22% self-reported significant depressive symptomatology following their injury. 20 Considering the prevalence and correlation of depressive symptoms in youth experiencing prolonged recovery from concussion, examination of these symptoms independent of other post-concussive symptoms is merited in order to understand their unique role in modifying the post-concussive symptom trajectory. This is particularly warranted given that depression is often treated differently, and sometimes under separate providers, than other post-injury symptoms.…”
Section: Introductionmentioning
confidence: 99%